Analysis Employee Productivity Based on the Characteristics of Workload, Motivation and Work Stress in Bakti Mulia Hospitals Muncar District Banyuwangi - Zainudin Efendi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Spotlight on the performance of nurses is a problem that must be addressed immediately, because nursing services determine the quality of hospital services. Poor performance will affect the low service, patients feel less comfortable and not satisfied that affect the productivity of work. Some causes of low work productivity include workload, motivation and work stress. The purpose of this research is to know the factors that influence productivity at Bakti Mulia Hospital Muncar of Banyuwangi Regency. The research design used was cross sectional. The research population is all employees at Bakti Mulia Muncar Banyuwangi Hospital as many as 133 people and sample size 100 people. The sampling technique using simple random sampling. Data collection using questioner then analyzed using logistic regression. The results show that there is the influence of the workload on work productivity (p = 0.012; OR = 0, 314), there is the influence of motivation to work productivity (p = 0.035; OR = 0, 035), there is the effect of work stress on work productivity at Bakti Mulia Hospital Muncar Banyuwang District (p = 0,0 3 9; OR = 0 , 102). While the most dominant factors that affect the productivity of employees at Bakti Mulia Hospital Muncar Banyuwangi regency is the work load. Based on the research, the management of hospital should consider the work load factor, motivation and work stress to increase work productivity and also to improve the facilities and infrastructures that support for the employees in the work.